ASUHAN KEPERAWATAN PASIEN STROKE HEMORAGIC DENGAN INTERVENSI INOVASI REPOSISI FIKSASI ETT TERHADAP PENCEGAHAN RESIKO TERJADINYA LUKA TEKAN MUKOSA MULUT DI RUANG ICU RSUD KAB TANGERANG - Yuli Irawati; Zahrah Maulidia Septimar; Andi Setiyawan (Yayasan Nusantara Hasana Berdikari, 2024)
Pressure ulcers on the mucous membrane are the location of wounds found on the mucous membrane with a history of using medical devices. Mucosal tissue is susceptible to pressure when using medical devices such as using oxygen tubes, endotracheal tubes, oropharyngeal tubes, orogastric and nasogastric tubes. This scientific paper aims to determine the effect of ETT fixation repositioning in ETT treatment to prevent the occurrence of pressure sores on the oral mucosa due to ETT installation in hemorrhagic stroke patients. Method providing nursing care intervention with innovative repositioning of ETT fixation to prevent the occurrence of pressure sores on the oral mucosa. Based on the case study, after carrying out nursing action in the form of ETT fixation repositioning, the result was that no pressure sores occurred on the patient's left lip area. After carrying out nursing actions by repositioning the ETT fixation for 3 days, the result was that there were no pressure sores on the patient's left lip area.